Cave millipeds of the United States. VI. Sequoiadesmus krejcae, n. gen., n. sp., from Sequoia and Kings Canyon National Parks, California, USA (Diplopoda, Polydesmida, Polydesmidea, Macrosternodesmidae) - Shear, William A.; Shelley, Rowland M. (Zootaxa, 2008)
Sequoiadesmus krejcae, n. gen., n. sp., a minute, depigmented polydesmidan milliped, is described from caves in Sequoia and Kings Canyon National Parks, Tulare County, California. It is provisionally assigned to the Macrosternodesmidae pending further research on representatives of the polydesmidean superfamilies Polydesmoidea and Trichopolydesmoidea in the western United States. Attributes of Macrosternodesmidae, Nearctodesmidae (Trichopolydesmoidea) and Polydesmidae (Polydesmoidea) are compared and contrasted.